STUDI METODE PELAKSANAAN PONDASI JEMBATAN KAYU DI SEI KARAU, KABUPATEN BARITO TIMUR (Study of the Implementation Methods of Wood Bridge in Sei Karau, East Barito District) - Maretina Eka Sinta; Jaro Lelond Tuah, S.T. (Huma Tabalien Jurnal (HTJ) Teknik Sipil, 2021)
Based on its function, a bridge is a structure that is made as an intermediary or link to cross /cross ravinesor obstacles such as rivers, railroads or roads, so to connect the city of Ampah which is splitby the Karau river, a bridge is needed. The object of research is a wooden bridge made by the Dutchcolonial in 1929 which still stands firmly and can be usedtoday, so to find out the method ofimplementation at the time of building the bridge, as well as to see the development of currentimplementation methods and resources, research was conducted to know the implementation methodspecifically for the installation of the foundation to find out the implementation technique and theequipment used.The research method used includes: (1) preliminary survey, (2) data collection and data analysis, (3)reconstruction of implementation methods, (4) delineation of reconstructed results.The results of the research study show that all stages of implementation use simple methods using simplemechanical equipment as well. In the case of the installation of the foundation, the executor takes intoaccount the placement of thepoint where the foundation is laid. The soil bearing capacity is estimated in asimple way.Keywords:History, Implementation Methods / Terms of Reference, Resources